DYNAMICS OF ACUTE CORONARY SYNDROME PATIENT MANAGEMENT IN NONIVASIVE PRIMARY VASCULAR CENTER (ACCORDING TO RECORD AND RECORD-2 REGISTERS) - V. M. Provotorov; I. Shevchenko; R. Islamov (Столичная издательская компания, 2016)
Aim. To study changes in acute coronary syndrome (ACS) patient hospital management in nonivasive primary vascular center in 2007-2009. Material and methods. 188 (RECORD register data) and 180 (RECORD-2 register data) patients with ACS were admitted to the emergency cardiology department in November 2007 and November 2009, respectively. Results. Thrombolytic therapy was performed in 62 patients in 2009 whereas in 2007 no one patient received this therapy because of thrombolytic drugs absence. Only 39.4% of patients were treated with unfractionated heparin in 2007. In 2009 50% of patients received unfractionated heparin, 12.5% of patients - enoxaparin and 7.4% - fondaparinux. 2.7% of ACS patients were transferred to the regional vascular center in 2007 and 3.9% -  in 2009. Conclusion. Creation of the primary vascular center led to improvement of ACS patient hospital management, and move it closer to modern guidelines. However hospital lethality did not changed (3.3% and 3.7% in 2009 and 2007, respectively).